2019
DOI: 10.1001/jamaophthalmol.2019.0449
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Polypoidal Lesions in Patients With Polypoidal Choroidal Vasculopathy Using Swept-Source Optical Coherence Tomographic Angiography

Abstract: IMPORTANCE Polypoidal choroidal vasculopathy (PCV) is a major cause of visual loss worldwide, particularly in Asia, and the appropriate understanding of the structures in PCV previously described as polypoidal lesions is important for understanding their pathogenesis, diagnosis, and prognosis. OBJECTIVE To report the morphologic characteristics of polypoidal lesions and their association with branching vascular networks (BVNs) in eyes with PCV using swept-source optical coherence tomographic angiography (SS-OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 39 publications
3
56
0
Order By: Relevance
“…In recent years, multimodal imaging technologies have allowed more precise views of polypoidal lesions and PCV choroids. Specifically, with optical coherence tomography angiography (OCTA), a novel imaging modality that reflects the choroid flow with higher accuracy and resolution compared to traditional dye-based ophthalmic angiography [4], emerging evidence suggests that the classical polypoidal lesions manifest as tangled vessels at the edge of BVN [5]. This finding further complicates our understanding of whether there is an actual difference between PCV and nAMD because the characteristic lesions of PCV and choroidal neovascularization (CNV) in nAMD are essentially both vascularization in nature and there might actually be no "polyps" or "aneurysmal vessels" [6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, multimodal imaging technologies have allowed more precise views of polypoidal lesions and PCV choroids. Specifically, with optical coherence tomography angiography (OCTA), a novel imaging modality that reflects the choroid flow with higher accuracy and resolution compared to traditional dye-based ophthalmic angiography [4], emerging evidence suggests that the classical polypoidal lesions manifest as tangled vessels at the edge of BVN [5]. This finding further complicates our understanding of whether there is an actual difference between PCV and nAMD because the characteristic lesions of PCV and choroidal neovascularization (CNV) in nAMD are essentially both vascularization in nature and there might actually be no "polyps" or "aneurysmal vessels" [6].…”
Section: Introductionmentioning
confidence: 99%
“…Potential reasons for the low detection rate of polyps in OCTA include the extra-macular location of polyps outside the central 6x6 mm area, segmentation errors, especially when there is highly elevated retinal pigment epithelium (RPE) detachment, and low vascular flow within the polyps [ 12 ]. Several studies have reported that the polyp detection rate of OCTA can be improved by adjusting the segmentation manually [ 5 7 , 9 , 10 ]. OCTA can detect flow with a velocity as low as 0.2~0.3 mm/s using a 70k-Hz A-scan within seconds [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, multi-model imaging technologies allows more precise view of polypoidal lesions and PCV choroid. Specifically, with optical coherence tomography angiography (OCTA), a novel imaging modality reflecting choroid flow with higher accuracy and resolution compared to traditional dye-based ophthalmic angiography(4), emerging evidence suggests the classical polypoidal lesions manifest as tangled vessels at the edge of BVN (5).…”
Section: Introductionmentioning
confidence: 99%